2005
DOI: 10.1007/s10494-005-6772-9
|View full text |Cite
|
Sign up to set email alerts
|

Swirling flow structures in electrostatic precipitator

Abstract: Stereoscopic digital Particle Image Velocimetry (PIV) has been used to make a threedimensional flow mapping of a volume of approximately 0.1 × 0.1 × 0.15 m in a laboratory model electrostatic precipitator (ESP). The mapped volume covers about two unit cells determined by the 100 mm electrode spacing in the 0.2 × 0.2 × 1.0 m ESP test section of the negative corona, barbed wire, smooth-plate kind. The barbs act as corona fix points, yielding a three-dimensional electrostatic field. The induced large-scale second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The current density with rotational component created vortices in the fluid. The modified vorticity equation and the Navier‐Stokes equation are shown as Equations and . ωixi=0, ρ[]ωit+vjωixj=μ2ωixj2+ωivixj1αεijkRkxj, where ω i is the vorticity, ρ is the fluid density, v i ( v j ) is the velocity, μ is the absolute viscosity, α is the ion mobility, and 1αεijkRkxj is the rotational component.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current density with rotational component created vortices in the fluid. The modified vorticity equation and the Navier‐Stokes equation are shown as Equations and . ωixi=0, ρ[]ωit+vjωixj=μ2ωixj2+ωivixj1αεijkRkxj, where ω i is the vorticity, ρ is the fluid density, v i ( v j ) is the velocity, μ is the absolute viscosity, α is the ion mobility, and 1αεijkRkxj is the rotational component.…”
Section: Resultsmentioning
confidence: 99%
“…Ullnm found that the EFA of “multineedles‐to‐plate” structure caused a large‐scale secondary flow, which would rotate in an unstable form along the axial of the emitting electrode to cause high intensity turbulence and axial velocity.…”
Section: Resultsmentioning
confidence: 99%